The Role of Auditors Against Money Laundering- Albania Case - Cika, Nertila; Dhamo, Sotiraq; Tola, Igli (European Journal of Economics and Business Studies, 2018)
In the process of the globalization of the economy one of the biggest challenges is combating and preventing criminal activities such as the money laundering. This phenomenon affects the failure of many sectors, such as monetary and banking system, the loss of public confidence in the financial system, the problem in calculating GDP in the affected countries. Albania has been considered a 'paradise' for investing and money laundering from suspicious or illegal activities, for more than 20 years. To prevent Money Laundering is necessary to make proper legislation and the involvement of several parties, including also the accounting professionals. The purpose of this paper is to estimate the role and function performed by Albanian Chartered Auditors (CAA –EKR) and auditors of State High Control Institution against Money Laundering. We try to give answer to the main research questions as: Are the Albanian auditors involved in fighting Money Laundering? Which is the level of legislation of Albania regulated against Money Laundering? What is the role of professional body of the auditors in preventing Money Laundering? The conclusions of this paper are based on literature review and data analysis through the independent test, Chi-Square test, gathered from questionnaires designed and intended for Albanian auditors to understand practically how they face this phenomenon in Albania. We find out a negligence of the auditors in reporting ML.Typically the construction companies with Albanian capital are involved in the money laundry transactions and further research studies are recommended to be made.
Keywords: money laundering, auditors, accounting professionals, procedure, financial statements